Mental health in HIV seronegative and seropositive IDUs in South Florida - Jones, Deborah L. (AIDS Care, 2010)
About one-third of HIV-infected people in the USA have a history of injection-drug use. Injecting drugs are a primary vector for HIV transmission. Drug and alcohol use are significant contributors to sexual transmission of the virus. In South Florida, urban injection-drug users (IDUs) represent a substantial population at risk for infection. Substance use management in this group is critical. As part of a larger study of at-risk populations in South Florida, we examined mental health differences among IDUs (n = 117), HIV seropositive IDUs (n = 130), and HIV seronegative non-IDUs (n = 169). We explored factors associated with depression and anxiety between groups, and found HIV seronegative and seropositive IDUs not receiving antiretroviral (ARV) treatment to have poorer overall mental health than both HIV seropositive participants on ARVs and non-IDU participants. Our data support systems enhancement to meet the various psychosocial and health care needs among IDUs and highlight the need for resource allocation to target community-based integrated mental health services in urban populations. In addition, our data underscore the need for primary and secondary HIV prevention interventions to address the drug-use risk behaviors among IDUs to reduce the likelihood of HIV infection and transmission in this population.